2021
DOI: 10.3389/fcvm.2021.777899
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Aspects, Prenatal Screening and Diagnosis of Congenital Heart Defects in Beijing

Abstract: Background: In China, congenital heart disease (CHD) is the most common birth defect type, with approximately 13,000 new cases annually. This study aimed to investigate high-risk factors, prenatal screening and prenatal diagnosis as a basis for clinical decisions.Methods: All CHD cases identified from 2018 to 2020 were obtained from the Beijing city birth defect surveillance system and prenatal diagnosis institutions. The prenatal CHD diagnosis was confirmed by fetal echocardiography and amniotic fluid or cord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
1
6
0
3
Order By: Relevance
“…Among the BDs, we found that CHD was the most common type of BD and its prevalence rate increased from 2.61 per 1000 births in 2018 to 4.56 per 1,000 births in 2020, the increase trend was consistent with the results of most previous studies in China and other countries (1,9,21). This phenomenon can be explained to some extent by the increasing proportion of older pregnant women, increasing social or natural environmental pressure, improvement in diagnostic techniques, for example, Bultrasound, and advances in the ascertainment of CHD (1,9). Although CHD was the most common type of BD in Guilin, the prevalence of CHD (total: 3.43 per 1,000 births) was still much lower than the global rate of 8-10 per 1,000 births (9).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Among the BDs, we found that CHD was the most common type of BD and its prevalence rate increased from 2.61 per 1000 births in 2018 to 4.56 per 1,000 births in 2020, the increase trend was consistent with the results of most previous studies in China and other countries (1,9,21). This phenomenon can be explained to some extent by the increasing proportion of older pregnant women, increasing social or natural environmental pressure, improvement in diagnostic techniques, for example, Bultrasound, and advances in the ascertainment of CHD (1,9). Although CHD was the most common type of BD in Guilin, the prevalence of CHD (total: 3.43 per 1,000 births) was still much lower than the global rate of 8-10 per 1,000 births (9).…”
Section: Discussionsupporting
confidence: 90%
“…Unfortunately, only 177 cases (8.84%) were assigned a known etiology in Guilin in 2018-2020, and the low proportion of BDs with known etiology may be attributed to several reasons. The first reason may be the low level of economic and technological development in Guilin; for example, although an increasing in the prevalence of genetic abnormalities in CHD patients was reported recently (2,9), only 1 in 507 CHD patients underwent genetic testing in Guilin (data not shown). Second, there was incomplete data collection and specialists in registered hospitals did not record some exposures (such as maternal infection, medication, pregestational diabetes) or query relevant information.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations